Systematic investigation of self-image-guided ultrasonic transceiver using time interval measurements for wireless power transfer. (March 2023) - Salahi, Rezvan; Moezzi, Mohsen; Ghafoorifard, Hassan; Kiani, Mehdi
Abstract: This paper presents a self-image-guided ultrasonic (SIG-US) system for wireless power transfer to miniaturized biomedical implants, in which time interval measurement (TIM) is employed on every other transducer. First, the conventional SIG-US method is investigated by the theoretical relations of ultrasound waves in the 2D environment and systematic simulations. Then the proposed TIM method is compared with the conventional SIG-US method. It is shown that this method can detect the implant's location with about halved power consumption, while the implant received power is approximately the same. Moreover, cascade and parallel methods for TIM among transducers are studied and compared. The implementation of the SIG-US method requires different blocks such as comparators to detect the start time of received signals and time to digital converters (such as a counter) to digitize measured delays. Passing from these blocks can lead to TIM errors. The effect of different types of TIM errors is studied to achieve the optimal specification of the proposed system. The simulation results show implant pressure loss is less than 1.6% for the parallel method with a 7-bit counter (15 MHz CLK) if the ratio of the reference voltage of comparators to their input amplitude and the ratio of offset voltage to reference voltage are assumed to be about 0.4 and 0.17, respectively. Highlights: The conventional self-image-guided ultrasonic (SIG-US) system for wireless power transfer was investigated using the theoretical relations of ultrasound waves in a 2D environment. The proposed time interval measurement (TIM) method on every other transducer can detect the implant's location with about halved power consumption, while the implant received power is approximately the same. Parallel and Cascade methods were studied and compared. The relationship between phase difference error and implant pressure reduction in the worst case was calculated for the conventional SIG-US method. The effect of different types of errors was investigated separately.